The Effect of Arthrospira Platensis on the Acute Toxicity of Artemeter Lumefantrine in Malaria Patients - Abdul Rahman Abid, Saim Sattar, Muhammad Hassan Saleem (Pakistan Journal of Medical & Health Sciences, 2022)
Malaria has remained one of the leading causes of morbidity and mortality in most developing countries. This pathology is caused by the Plasmodium spp. Artemisinin-based combination therapy is recommended by current WHO guidelines for the treatment of uncomplicated falciparum malaria (ACT). -Linolenic acid, one of the necessary fatty acids, is abundant in the microscopic filamentous alga Arthrospira platensis, which is rich in proteins, vitamins, vital amino acids, and minerals (GLA). The current study was carried out to evaluate the effect of Arthrospira platensis on the liver and kidney toxicity induced by ACT. Malaria patients were randomized into two groups to receive therapeutic dose of either artemether-lumefantrine 20/120mg (group 1) or artemether-lumefantrine 20/120mg + Arthrospira platensis 8g daily (group2) as an adjunct therapy and follow-up for 7 days. After treatment their liver and kidney Biochemical parameters (ALT, AST, ALB, UREA, CREAT) were measured. Both pre and post treatment samples were analyzed and the results gotten compared with control group made up of malaria negative patients. Serum activity of selected biomarkers (ALT, AST, ALB, UREA) of malaria patients were seen to be statistically significant (P<0.05) on D0 when compared to that of malaria negative patients. This study showed that Arthrospira platensis prevented the artemether-lumefantrine induced significant changes on the liver and kidney biochemical parameters analyzed. The results obtained from this study, indicate that Arthrospira platensis has a positive effect on the liver and kidney toxicity induced by ACT and hence could be administered together with ACT in malaria treatment.